Decision‐makers are resilient in the face of social exclusion. - Juanchich, Marie; Sirota, Miroslav; Walasek, Lukasz (British Journal of Psychology, 2018)
A growing body of evidence suggests that social exclusion impairs people's capacity for active deliberation and logical reasoning. Building on this finding and on the postulate from the dual‐process theory that analytical thinking is essential in order to make good judgements and decisions, we hypothesized that social exclusion will alter judgement and choice behaviour. We tested this hypothesis in three experiments in which social exclusion was manipulated using the Cyberball paradigm, an online ball‐tossing game in which participants either received the ball a fair number of times or were excluded by the other two players. We focused on a range of tasks designed to be sensitive to participants’ ability to engage in analytical thinking and careful deliberation, including the cognitive reflection test (Experiment 1) and a set of anchoring, intertemporal preference, disjunction, and confidence tasks (experiments 2 and 3). Our results unanimously failed to support the hypothesis that social exclusion influences people's judgements and decision‐making. We discuss the implications of our findings for social exclusion theory.